Keragaan Agronomi dan Potensi Hasil Genotipe Jagung (Zea mays L.) Generasi S1 dan S2 di Dua Lokasi - Salamah, Umi; Suwarno, Willy Bayuardi; Aswidinnoor, Hajrial; Nindita, dan Anggi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Hybrid maize breeding relies on the availability of good performing inbred lines with superior combining ability. The objectives of this study were to: (1) estimate genetic paramters and heritability for agronomic and yield traits, (2) estimate correlations among traits, and (3) estimate selection-balanced inbreeding depression level from S1 to S2 generations. The S1 trial was planted from June to September 2014 at two locations, followed by the S2 trial from January to May 2015 at the same locations. Each trials was arranged in an augmented design with three blocks consisting of 72 unreplicated test genotypes, 3 unreplicated inbred lines, and 5 replicated commercial hybrid varieties as checks. The results showed that the heritability estimates were medium to high for most observed traits. Best yielding genotypes in S1 and S2 generations were derived from P27xNK6326, Pertiwi3xP31, NK6326xP31, P31xNK6326, and P31xNK33 populations. Grain yield was positively correlated with plant height, ear height, ear length, and ear diameter in S1 and S2 generations. The S2 generation exhibited inbreeding depression for grain yield. The estimates of heritability, correlations, and inbreeding depression obtained from this study could be useful for selection in corn breeding programs.Keywords: correlation, heritability, inbreeding depression